The morphometric analysis of ossicula auditus in malakan horses - İftar Gürbüz; Mevlüt Aykut; M. Orhun Dayan; Kadir Aslan (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study is to determine morphometrically the differences of the auditory ossicles of Malakan Horses according to their gender. Materials and Methods: In the study 10 (5 male, 5 female) adult Malakan Horses? auditory ossicles were used. 15 different morphometric values were measured on the auditory ossicles, which removed from the skull. The morphometric values were compared in terms of gender and direction (left, right). Results: The malleus lengths were 9.97±1.27-10.05±1.15 mm, incus length were 4.11±0.70-3.65±0.20 mm, stapes length were 3.25±0.51-3.43±0.22 mm in male and female Malakan Horses respectively. The values of incus width and incus height were significantly higher in males than females (P< 0.05). In terms of all the other measurements, the differences between the genders and direction (left, right) were not statistically significant (P> 0.05). Conclusions: It was concluded that, there were no statistically differences of morphometric values on auditory ossicles except the values of incus width and incus height in Malakan Horses according to gender.